2018
DOI: 10.6118/jmm.2018.24.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Pathological Mechanisms of Insomnia and Osteoporosis, and a New Perspective on Safe Drug Choice

Abstract: Lack of adequate sleep has become increasingly common in our 24/7 modern society. Reduced sleep has significant health consequences including metabolic and cardiovascular disorders, and mental problems including depression. In addition, although the increase in life expectancy has provided a dream of longevity to humans, the occurrence of osteoporosis is a big obstacle to this dream for both male and female. It is known that insomnia and bone health problems, which are very critical conditions in human life, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Thus, a combined low BMD and TBS representing the high frequency of osteoporotic fractures may be associated with insomnia [ 214 ]. The underlying possible mechanisms may include insomnia-mediated dysregulation of the hypothalamo-pituitary-adrenal (HPA) axis due to increased secretion of cortisol, altered levels of hormones (orexins, ghrelin, serotonin, melatonin), and stress-related metabolic alterations with its resultant impact on the sympathetic system [ 215 ].…”
Section: Common Complications Of Insomniamentioning
confidence: 99%
“…Thus, a combined low BMD and TBS representing the high frequency of osteoporotic fractures may be associated with insomnia [ 214 ]. The underlying possible mechanisms may include insomnia-mediated dysregulation of the hypothalamo-pituitary-adrenal (HPA) axis due to increased secretion of cortisol, altered levels of hormones (orexins, ghrelin, serotonin, melatonin), and stress-related metabolic alterations with its resultant impact on the sympathetic system [ 215 ].…”
Section: Common Complications Of Insomniamentioning
confidence: 99%
“…Several studies have shown associations between inadequate nocturnal sleep and negative health factors ( Foley et al, 2004 ; Goldman et al, 2007 ). In fact, repetitive sleep deprivation (<6 hours/day) is associated with endocrine and immune dysregulations and cognitive decline ( Tumiran et al, 2018 ), which increase the prevalence of chronic diseases such as diabetes ( Tan et al, 2018 ), metabolic syndrome ( Tan et al, 2018 ), obesity ( Tan et al, 2019 ), osteoporosis ( Yi et al, 2018 ), heart disease ( Foley et al, 2004 ), neurodegenerative diseases ( Wei et al, 2019 ), and even mortality ( Stone et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%